Pengaruh Pembelajaran Berbasis Gamifikasi Terhadap Penguasaan Konsep dan Motivasi Siswa pada Materi Siklus Air - Rostiani, Ani; Sujana, Atep; Jayadinata, Asep Kurnia (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The aim of this research is to analyze the influence of gamification-based learning with conventional learning on class V students' mastery of concepts. The quasi-experimental method used in this research. Inferential statistical analysis and descriptive statistics using Microsoft Excel 2016 and SPSS version 20 were used for data processing. Sampling used purposive sampling technique with 31 students from class V-A control class and 33 students from class V-B experimental class. Research findings show that gamification-based learning has a positive effect on students' concept mastery and motivation. Students' mastery of concepts increased from an average score of 56.991 to 80.191. Students' learning motivation after applying gamification-based learning did not increase. The t-test results obtained were sig. = 0.593 â‰¥ 0.05. Gamification-based learning has a better effect on students' mastery of concepts compared to conventional learning as seen from the t-test results with an average in the experimental class of 80.358 > 72.97 in the control class.